A prospective study of outcome in infertility patients diagnosed with genital tuberculosis - Yadav, Sumitra; Kumar, Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Tuberculosis is an increasing health problem worldwide with around 9.6 billion new cases reported every year. Female genital tuberculosis (FGTB) has a varying incidence ranging from a very low of 0.69% in developed nations to as high as 19% in developing nations like India. The average incidence of infertility due to tuberculosis is 5-10% worldwide. Methods: The study was a hospital based prospective clinical study, from September 2014-2017 with sample size of 355 infertility cases. Endometrial sampling and diagnostic hystero-laparoscopy were used for diagnosis. Endometrial sample subjected for both the test CBNAAT and HPR was used for confirmation of positive patients. Inclusion criteria were, infertile patients diagnosed with genital tuberculosis who were then given treatment. Patients diagnosed to have infertility due to causes other than TB were excluded from the study. Highly suspected cases and those who were willing underwent diagnostic laparoscopy. Results: Out of 355 cases of infertility, 83 were because of genital TB, received treatment out of which 32 conceived. CBNAAT was very sensitive than histopathology or laparoscopy. The live birth rate and conception rate were 20.24% and 38.09 % respectively. Conclusions: CBNAAT is OPD based economical test (free by GOI), very sensitive and picked up more cases than histopathology or laparoscopy. The live birth rate and conception rate were found to be higher than other studies possible due to intervention at an earlier stage of the disease process. This test should be widely used by gynecologist for early detection of genital tuberculosis.